Carotid Artery Ultrasonographic Assessment in Patients from the Fremantle Diabetes Study Phase II with Carotid Bruits Detected by Electronic Auscultation - Knapp, Arthur (Mary Ann Liebert, Inc., 2014)
Background: Electronic auscultation appears superior to acoustic auscultation for identifying hemodynamic abnormalities. The aim of this study was to determine whether carotid bruits detected by electronic stethoscope in patients with diabetes are associated with stenoses and increased carotid intima-medial thickness (CIMT). Subjects and Methods: Fifty Fremantle Diabetes Study patients (mean±SD age, 73.7±10.0 years; 38.0% males) with a bruit found by electronic auscultation and 50 age- and sex-matched patients with normal carotid sounds were studied. The degree of stenosis and CIMT were assessed from duplex ultrasonography. Results: Patients with a bruit were more likely to have stenosis of ≥50% and CIMT of >1.0 mm than those without (odds ratios [95% confidence intervals]=14.0 [1.8–106.5] and 5.3 [1.8–15.3], respectively; both P=0.001). For the six patients with stenosis of ≥70%, five had a bruit, and one (with a known total occlusion) did not (odds ratio=5.0 [0.6–42.8]; P=0.22). The sensitivity and specificity of carotid bruit for stenoses of ≥50% were 88% and 58%, respectively; respective values for stenoses of ≥70% were 83% and 52%. The equivalent negative predictive values were 96% and 98%, and positive predictive values were 30% and 10%, respectively. Conclusions: Electronic recording of carotid sounds for later interpretation is convenient and reliable. Most patients with stenoses had an overlying bruit. Most bruits were false positives, but ultrasonography is justified to document extent of disease; CIMT measurement will identify increased vascular risk in most of these patients. The absence of a bruit was rarely a false-negative finding, suggesting that these patients can usually be reassured that they do not have hemodynamically important stenosis.